Pengaruh Image Engagement pada Aplikasi Parasit Malaria - Muhammad Irsan Sabir; Muhammad Niswar; Indrabayu Indrabayu (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2018)
The mosquito's parasite is a group of single-celled microorganisms in the plasmodium type that can cause malaria by attacking human blood cells. In this study, a parasitic detection application of Plasmodium Falciparum type at thropozoite, scizont and gametocyte stage was designed using Android Studio 2.2.2 and OpenCV 2.4.9 library. Image detection process begins with preprocessing, then feature extraction and classification phase using Haar Cascade Classifier, then the last stage 3 types of boost compared, namely Gentle Adaboost, Discrete Adaboost, and Real Adaboost. Image Enhancement is one of the preliminary processes in preprocessing that aims to clarify certain features or features of the image to be more easily analyzed carefully in the feature selection process. The results of this study prove that image enhancement can be used to improve image quality so that the information available on the image can be seen more clearly.